Probing charge transfer dynamics in self-assembled monolayers by core hole clock approach - Zharnikov, Michael (Journal of electron spectroscopy and related phenomena, 2015)
This article reviews recent progress in the application of core hole clock approach in the framework of resonant Auger electron spectroscopy to the monomolecular assembles of alkyl, oligophenyl, and oligo(phenylene-ethynylene) based molecules on Au(111) substrates, referring mostly to the work by the author et al. The major goal was to study electron transfer (ET) dynamics in these systems serving as prototypes of molecular electronics (ME) devices. The ET pathway to the conductive substrate was unambiguously defined by resonant excitation of the nitrile tailgroup attached to the molecular backbone. Characteristic ET times within the femtosecond domain were determined, along with the attenuation factors for the ET dynamics, analogous to the case of the static transport. The above parameters were found to exhibit strong dependence on the character of the molecular orbital which mediates the ET process. In addition, certain spectral features, which can be associated with an inverse ET from the molecular backbone to the excitation site, were observed upon exchange of the nitrile group by strongly electronegative nitro moiety. The reported results represent a valuable input for theory and a certain potential for applications such as ME devices where optimization of ET can have significant technological impact.
Gesehen am 04.08.2020